2019
DOI: 10.1016/j.burns.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life 5–7 years after minor and severe burn injuries: a multicentre cross-sectional study

Abstract: Introduction Burn injury can affect health-related quality of life (HRQL). Knowledge concerning long-term HRQL in burn patients is limited. Therefore, our aim was to evaluate long-term HRQL and to study predictors of impaired long-term HRQL. Methods All adults with a length of stay (LOS) of ≥1 day (2011-2012) were invited. Also, adults with severe burns, i.e. >20% total body surface area (TBSA) burned or TBSA full thickness>5% (2010-2013) were invited. Participants completed the EuroQol(EQ)-5D-5L+C and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…HRQL data from the ten different studies originated from five countries, namely Belgium, Germany, Norway, Sweden and The Netherlands [4,9,10,24,25,[31][32][33][34][35]. Data was collected between 1995 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HRQL data from the ten different studies originated from five countries, namely Belgium, Germany, Norway, Sweden and The Netherlands [4,9,10,24,25,[31][32][33][34][35]. Data was collected between 1995 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Studies focusing on other outcomes in burns found that female burn patients had higher levels of fatigue, a worse opinion about their scars, more difficulties with social participation, and mortality rates are higher than in male patients [46][47][48][49]. With respect to longer LOS, many studies have shown that patients with a prolonged hospital stay have a diminished HRQL, both shortly and longer after burns [10,41]. This is also in line with results from the general trauma population, where LOS has also been found to influence HRQL after injury [50,51].…”
Section: Measurement Point No Of Studies Contributing No Of Patients mentioning
confidence: 99%
See 1 more Smart Citation
“…Lifelong disability was assumed when a patient reported a severe problem (level 3 EQ-5D-3 L) in any of the five EQ-5D-3 L dimensions or mild problems (level 2 EQ-5D-3 L) for both the dimensions pain/discomfort and anxiety/depression at two-year follow-up. These two dimensions were chosen based on literature; these dimensions are most often affected by burns [13,15]. The percentage of patients with lifelong disabilities was assessed from the combined dataset.…”
Section: Health-related Quality Of Life Measuresmentioning
confidence: 99%
“…Up to 24 months post-burn, most limitations improve, however, some remain highly prevalent in a subset of patients in the long-term, like psychological functioning [13]. Moreover, there are apparent latent limitations, like participation restrictions due to mental well-being, which tend to develop after physical symptoms subside [13][14][15]. In the recent Global Burden of Disease (GBD) study the burden associated with burn injuries has been included [16].…”
Section: Introductionmentioning
confidence: 99%